Desain Kompresor Multi-tahap untuk Optimalisasi Produksi Gas Lapangan X - Dwi Astitie Indah Sari (Fakultas Teknik, 2025)
Field X is a gas field that has been producing for decades and is currently experiencing a significant drop in reservoir pressure. The two-stage compressor system implemented since 2017 has proven effective in increasing the gas production rate which had dropped to 4.45 MMscfd, with the target of increasing production back to the range of 5 to 10 MMscfd. However, entering the end of 2024, this system is no longer able to maintain the required flow pressure, so production drops again. This study aims to evaluate the performance of the three-stage compressor system as a technical solution, as well as predict gas production trends after the implementation of the new system using the integrative approach of Decline Curve Analysis (DCA), Inflow Performance Relationship (IPR), and Vertical Lift Performance (VLP). The results of the evaluation showed that the two stage system experienced pressure limitations and outlet pressure that did not meet the distribution specifications. The three-stage compressor design has been proven to be able to significantly lower the wellhead pressure and reach the inflow-outflow equilibrium point with a production rate of up to 9 MMscfd. DCA projections show that this system is able to slow the rate of production decline until 2030. Thus, replacing the two-stage compressor system with a three-stage is an effective and sustainable technical solution in maintaining Field X gas production according to the contract target..
Reaploud Repository April 2026
Keywords: three-stage compressor; wellhead pressure; Decline Curve Analysis; Inflow Performance Relationship; Vertical Lift Performance